Mortgage Finance in Central and Eastern Europe : Opportunity or Burden? - Beck, Thorsten; Tiongson, Erwin; Kibuuka, Katie (World Bank, Washington, DC, 2014)
Household credit, especially for mortgages, has doubled over the past years in the new European Union member countries, raising concerns about the economic and social consequences of household indebtedness in the event of a macroeconomic crisis. Using household survey data for 2005, 2006, and 2007 for both old and new European Union members, this paper assesses the determinants of access to mortgage finance. It also examines whether mortgage holders were more likely to suffer financial distress compared with non-mortgage holders in the period before the global financial crisis. The analysis does not find any systematic evidence that mortgage holders are financially more vulnerable than renters or outright owners; in fact, the incidence of financial vulnerability generally fell between 2005 and 2007, possibly reflecting the strong income growth experienced by these countries over this period. In addition, although tenure status is more difficult to explain in the new European Union member countries, the analysis finds that many of the same drivers of tenure status in the older member countries generally drive tenure status in the newer member countries as well. Finally, there is no evidence that access to mortgage credit is based on expected income in the old or in the new European Union member countries.